Diagnostic Value of 1.5T MRI in Differentiating Acute and Chronic Osteomyelitis in Diabetic Patients: A Meta-Analysis - Piyush Kant; Swati Bansal; Tarun Kumar; Vanshika; Gopi Kishan; Santosh Kumar; Rohit Bansal (The Bioscan, 2026)
Purpose: The aim of the review is to determine the usefulness of 1.5 T MRI in the distinction between acute and chronic osteomyelitis in diabetic patients, as an essential differentiation in order to achieve better results of treatment. Methods: A meta-analysis and systematic review were done according to PRISMA guidelines. Articles published between January 2010 & May 2025 in Scopus, PubMed, ResearchGate, and Web of Science were searched. Inclusion criteria encompassed peer-reviewed studies involving diabetic patients with osteomyelitis, utilising 1.5 T MRI, and providing data on differentiation between acute and chronic forms. Diagnostic accuracy metrics were aggregated using a bivariate random-effects model, and heterogeneity was assessed with the I² statistic. Results: From 1,200 identified records, 25 studies fulfil the inclusion criteria, comprising 1,500 patients. The meta-analysis revealed a sensitivity of 92% (95% CI: 88–95%) and a specificity of 85% (95% CI: 80–89%) for 1.5 T MRI in diagnosing osteomyelitis. Acute osteomyelitis was characterised by bone marrow oedema (sensitivity: 95%, specificity: 70%), while chronic osteomyelitis was marked by sequestrum (sensitivity: 60%, specificity: 98%). Gadolinium-enhanced sequences improved sensitivity for acute cases. Significant heterogeneity (I² = 60–65%) was observed, partly attributable to variations in MRI protocols and reference standards. Conclusion: 1.5 T MRI demonstrates high diagnostic accuracy in differentiating acute and chronic osteomyelitis in diabetic patients, with distinct imaging features aiding clinical decision-making. Standardisation of MRI protocols and further research in advance imaging techniques are recommended to enhance diagnostic precision. KEYWORDS 1.5 Tesla MRI, Diabetic foot osteomyelitis, Acute vs chronic osteomyelitis, Magnetic resonance imaging in diabetes, Diagnostic accuracy of MRI, Meta-analysis of osteomyelitis diagnosis